CEO overconfidence and financial crisis: Evidence from bank lending and leverage - Ho, Po-Hsin; Huang, Chia-Wei; Lin, Chih-Yung; Yen, Ju-Fang (Journal of Financial Economics, 2016)
Over a period that includes the 1998 Russian crisis and 2007–2009 financial crisis,banks with overconfident chief executive officers (CEOs) were more likely to weaken lending standards and increase leverage than other banksin advance of a crisis,making them more vulnerable to the shock of the crisis.During crisis years, they generally experienced more increases in loan defaults, greater drops in operating and stock return performance, greater increases in expected default probability, and higher likelihood of CEO turnover or failure than other banks.CEO overconfidence thus canexplain the cross-sectional heterogeneity in risk-taking behavior among banks.